Science and Religion: Enemies for life? - Ciliberti, Rosagemma; Tesi, Chiara; Fusco, Roberta; Bonsignore, Alessandro; Licata, Marta (Acta Biomedica Atenei Parmensis, 2019)
The article published by Prof. Antonio Neviani in 1896 offered us an interesting opportunity to discuss about the teaching of human evolution in schools today. Already at the end of the nineteenth century, Neviani complained about the fact that the teaching of the theory of evolution was not present in schools. Here, we present the thought of Neviani and we invite to reflect on the prohibition, still present in some countries, of the teaching of Darwin’s theory. (www.actabiomedica.it)